Aplikasi Pembelajaran Trigonometri Berbasis Android Menggunakan Algoritma Fisher Yates Shuffle - Akbar Gani; Linda Marlinda (Universitas Bina Sarana Informatika, 2017)
With the development of technologies, applications, a sort of mobile devices can be created and developed on Android a few ways to overcome misconceptions students and teachers, as well as to enhance meaningful learning among other things, facilitate the learning of conceptual depth, connecting the prerequisite knowledge with new knowledge, as well as using a tool (instrument / media) of cognitive mengkongkritkan abstract concepts. Moreover, as the development time has been developing mobile phones. The purpose of making this program other than to make the thesis, as well as to produce Android-Based Application of Learning trigonometry. With the Fisher-Yates Shuffle method, which is implemented as an alternative media other than books and print media on the android operating system based smartphone